O transtorno mental na percepção de agentes comunitários de saúde na estratégia saúde da família - Vitta, Fabiana Cristina Frigieri de [UNESP]; Oliveira, Odilente Ferreira; Gatti, Márcia A. Nuevo; Vitta, Alberto de (My University, 2012)
The Family Health Strategy facilitates user access to mental health actions. This study aimed to verify the community health agents’ perceptions of the Family Health Strategy about mental disorder. A qualitative study was conducted with 26 randomly selected community health agents, among the professionals of 13 units, which constitute the Family Health Strategy of Itapeva (SP). The community health agents responded to a personal information questionnaire and a semi-structured interview. Data were checked through content analysis. Stigmatizing perception of the mentally disturbed persons, lack of knowledge about the process of falling ill and the mental disorder evolution, and the unpreparedness to act in this population were observed. Capacitating agents enable them to contribute in a positive way to the effective functioning of a care net in mental health in the city.

A Estratégia Saúde da Família facilita o acesso do usuário às ações de saúde mental. O objetivo deste estudo foi verificar as percepções dos agentes comunitários de saúde da Estratégia Saúde da Família em relação à doença mental. Realizou-se um estudo qualitativo com 26 agentes comunitários de saúde sorteados entre os profissionais de 13 unidades da Estratégia Saúde da Família do Município de Itapeva (SP), que responderam ao questionário de informações pessoais e entrevista semiestrutura. A análise foi realizada por meio do conteúdo dos dados. Percepção estigmatizada do portador do transtorno mental, falta de conhecimento sobre o processo de adoecimento e evolução da doença, e despreparo para atuar junto dessa população foram observados. É necessária a capacitação dos agentes para que eles possam contribuir favoravelmente para a eficiência da rede de cuidados em saúde mental no município.
The mental disorder in the perception of the community health agents in the Family Health Strategy